Activation cross sections of proton and deuteron induced nuclear reactions on holmium and erbium, related to the production of 161Er and 160Er medical isotopes. (September 2016) - Tárkányi, F.; Ditrói, F.; Takács, S.; Hermanne, A.; Baba, M.
Abstract: Experimental excitation functions for long-lived products in proton induced reactions were measured with the activation method in the 37–65 MeV energy range on natural holmium. Stacked foil irradiation technique and high resolution gamma spectrometry were used in order to measure cross-section data for the production of 161 Er, 160 Er and 1 59, 157 Dy. For comparison of the production routes of medically related 161 Er and 160 Er radioisotopes new experimental cross section data were deduced for the 162 Er(p, x) 161, 160 Er and 162 Er(d, x) 161, 160 Er reactions by re-evaluating gamma-ray spectra from earlier measurements. No earlier data were found in the literature for these reactions. The experimental data are compared with results of TALYS theoretical code reported in TENDL-2015. Highlights: Proton and deuteron induced reactions holmium and erbium. Stacked foil irradiations. Comparison of experimental results with the TENDL libraries. 161 Er and 160 Er medical radioisotope production routes.